2015
DOI: 10.3348/kjr.2015.16.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Whole Body MR/PET: Where Are We?

Abstract: Whole body integrated magnetic resonance imaging (MR)/positron emission tomography (PET) imaging systems have recently become available for clinical use and are currently being used to explore whether the combined anatomic and functional capabilities of MR imaging and the metabolic information of PET provide new insight into disease phenotypes and biology, and provide a better assessment of oncologic diseases at a lower radiation dose than a CT. This review provides an overview of the technical background of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 101 publications
(194 reference statements)
0
45
0
Order By: Relevance
“…Instead, PET coupled with CT or MRI is often used, as these dual-imaging techniques reveal both anatomical and functional molecular information. Though PET/CT is the traditional form of dual-modal imaging, PET/MRI has recently gained popularity in cancer imaging, as certain types of cancers (e.g., brain, head, neck) are better visualized by MRI than by CT [180]. For example, a study demonstrated that radioisotope-bearing nano micelles can be constructed and used for the treatment and imaging of rat GBMs.…”
Section: Application Of Nanotechnology For Brain Cancer Imagingmentioning
confidence: 99%
“…Instead, PET coupled with CT or MRI is often used, as these dual-imaging techniques reveal both anatomical and functional molecular information. Though PET/CT is the traditional form of dual-modal imaging, PET/MRI has recently gained popularity in cancer imaging, as certain types of cancers (e.g., brain, head, neck) are better visualized by MRI than by CT [180]. For example, a study demonstrated that radioisotope-bearing nano micelles can be constructed and used for the treatment and imaging of rat GBMs.…”
Section: Application Of Nanotechnology For Brain Cancer Imagingmentioning
confidence: 99%
“…To generate artifact‐free, quantitatively accurate PET images, attenuation and scatter correction is of crucial importance . In the combined PET/CT scanner, a PET attenuation map at 511 KeV is generated from X‐ray CT images using a piece‐wire, linear transformation function . As both the emitted 511 KeV photon pairs in the PET scan and X‐rays in the CT scan are attenuated during penetration of the body structure, attenuation correction in PET/CT is somewhat straightforward.…”
Section: Technical Considerations For Whole‐body Pet/mrimentioning
confidence: 99%
“…As both the emitted 511 KeV photon pairs in the PET scan and X‐rays in the CT scan are attenuated during penetration of the body structure, attenuation correction in PET/CT is somewhat straightforward. However, MRI‐based PET attenuation correction is much more complicated, as the MRI signal is largely determined by the tissue's hydrogen density and relaxation properties, not by the depth of body structures . In addition, MRI RF coils placed above the PET detectors in an integrated scanner can cause serious attenuation of 511 KeV photons generated from the radiotracers .…”
Section: Technical Considerations For Whole‐body Pet/mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic accuracy can be significantly enhanced by combining two approaches, introduced as “hybrid technology” in the filed of cancer imaging (Cherry, 2009; Yoo, Lee, & Lee, 2015). PET/CT, an example of this hybrid technology which utilizes the metabolic information of PET with the anatomic detail of CT, which overcomes the inherent barriers of the individual approach.…”
Section: Approaches Used To Detect Metastatic Lesions (On a Clinicmentioning
confidence: 99%